Antibacterial Activity Test Against Cutibacterium acne and Contaminant Testing of Spirulina (Arthrospira platensis) Anti-Acne Serum - Hilma Putri; Phebe Hendra (Sanata Dharma University, 2026)
Acne is a skin problem caused by the Cutibacterium acne bacteria, which has increasing bacterial resistance. Therefore, this study aims to evaluate the antibacterial activity of spirulina extract serum against C. acne, as well as to test for microbial contamination, heavy metals, and microplastics in the serum. Antibacterial activity tests were conducted using the well diffusion method with varying concentrations of spirulina extract (0.25%, 0.5%, and 1%) compared to the positive control clindamycin. Microbial and heavy metal contamination tests were conducted based on standard laboratory methods. Verify microplastic-free status using the